LibrasDetec: um Componente de Detecção de Movimentos para Karaokê em Libras - Lima, Manuella Aschoff; França, Daniel de; Silva Neto, Arnor da; Souza, Daniel Faustino de; Omaia, Derzu; Araújo, Tiago Maritan de (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2025.15182, 2025)
The entertainment market has been expanding rapidly, driven in part by increased internet access, which has also contributed to the growth of the digital games industry. However, despite this expansion, investments in accessibility remain limited, compromising the quality of games for people with disabilities. In the context of entertainment or serious games, particularly regarding accessibility for deaf users, motion detection emerges as a promising strategy to enable interaction through gestures in their native language. In this scenario, we propose LibrasDetec, a component for detecting and evaluating Brazilian Sign Language (Libras) gestures, integrated into the educational game Libraskê. The solution captures user gestures via webcam and compares them with reference videos, providing real-time scoring. To validate the proposed component, we conducted tests with 12 participants from three different user profiles: deaf individuals, interpreters, and non-signers. The results showed a satisfactory alignment between automated and human evaluations, especially among deaf users, suggesting that LibrasDetec is a viable approach to enhance accessibility and engagement in serious games focused on Libras.